Pneumomediastinum after Tooth Extraction - Ilhan Ocakcioglu; Serhat Koyuncu; Mustafa Kupeli; Oguzhan Bol (Case Reports in Surgery)
Pneumomediastinum is defined as the presence of air in mediastinum. Pneumomediastinum can sometimes occur after surgery. Pneumomediastinum seen after dental procedures is rare. We presented the case of subcutaneous emphysema developed in the neck and upper chest after tooth extraction and discussed the possible mechanisms of pneumomediastinum.